2015
DOI: 10.1353/hpn.2015.0094
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Cultural and Linguistic Competence with Documentary Film in Spanish

Abstract: The 2007 MLA report “Foreign Language and Higher Education: New Structures for a Changed World,” with its call to institutions of higher education to reexamine their curricula and include more in-depth cultural content into all courses, reminded foreign language educators of the important goal of helping students gain translingual/transcultural competence. Finding appropriate teaching tools to attain this goal, however, is often challenging for instructors since textbooks tend to focus primarily on vocabulary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…The benefits of using target language films and videos in foreign language (FL) teaching was first discussed in the 1990s when a group of French learners were instructed with the help of videos (Secules et al, 1992). In the 2010s, researchers examined the effects of films used as textbooks (Hertel & Harrington, 2015) as well as films as supplementary teaching tools (Rouxel-Cubberly, 2014). These studies showed positive results regarding in-class video use.…”
Section: Learning Efl Through Films and Social Mediamentioning
confidence: 99%
“…The benefits of using target language films and videos in foreign language (FL) teaching was first discussed in the 1990s when a group of French learners were instructed with the help of videos (Secules et al, 1992). In the 2010s, researchers examined the effects of films used as textbooks (Hertel & Harrington, 2015) as well as films as supplementary teaching tools (Rouxel-Cubberly, 2014). These studies showed positive results regarding in-class video use.…”
Section: Learning Efl Through Films and Social Mediamentioning
confidence: 99%
“…The benefits of using target language films and videos in foreign language (FL) teaching was first discussed in the 1990s when a group of French learners were instructed with the help of videos (Secules et al, 1992). In the 2010s, researchers examined the effects of films used as textbooks (Hertel & Harrington, 2015) as well as films as supplementary teaching tools (Rouxel-Cubberly, 2014). These studies showed positive results regarding in-class video use.…”
Section: Learning Efl Through Films and Social Mediamentioning
confidence: 99%
“…En la revisión realizada se detectaron 107 segmentos codificados en relación con el uso de la tecnología, la cual se ha convertido en una aliada para apoyar los procesos de enseñanza-aprendizaje de todas las áreas y la didáctica de la lengua no es la excepción. En los artículos objeto de estudio aparecieron recursos tecnológicos para desarrollar la competencia comunicativa, como la gamificación (Rachels y Rockinson-Szapkiw, 2018), redes sociales (Piriyasurawong, 2019), herramientas virtuales adaptadas al contexto académico (Rodrigo, 2017), edublogs , uso de películas (Hertel y Harrington, 2015), videos musicales (Sánchez-Vizcaíno y Mora, 2018), canciones (Hornillos y Roa, 2015), diseño de telediarios (Hernández Liechti, 2017) y otros proyectos. Sin embargo, llama la atención lo que sostienen (González Martínez et al, 2015) en una de las conclusiones de su estudio: no siempre la tecnología empleada contribuye con la mejora de las habilidades textuales.…”
Section: Enfoques Y Tendencias Metodológicasunclassified